Yobagi: Platform Market UMKM Berbasis Kewirausahaan Sosial - Dwi Yuny Sylfania; Rendy Rian Chrisna Putra; Fransiskus Panca Juniawan; Muhammad Intan Arfies; Nadila Fasya Anggraeni; Dehan Permata Sari; Aqilla Fadiya Haya; Deriza Nabilah Fitria (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2022)
The presence of the Covid-19 pandemic has had a major impact on the people of the Bangka Belitung Islands Province. There have been many layoffs for some communities which have resulted in a decline in their economy. Another impact was felt by Micro, Small and Medium Enterprises (MSMEs) where their sales transactions also decreased. Yobagi is proposed to overcome this problem by becoming a social entrepreneurship-based platform that becomes an intermediary medium for anyone who has the desire to share their skills, knowledge, and experiences. Yobagi is also a marketplace for MSMEs to promote their products or services. The purpose of developing Yobagi is to increase community skills and be able to innovate so that they can run new businesses to improve the economy. This study uses a prototype research method which consists of five stages, namely Communication, Quick Plan, Modeling Quick Plan, Construction of Prototype, and Deployment. The result of the research is a web-based Yobagi application that functions well, as evidenced by a functional test using the Blackbox method. Furthermore, the Responsive Web Design (RWD) feature on the Yobagi system was also tested to test the performance of features on several different types of smartphones.